Особливості забезпечення відмовостійкості в Cloud, Fog та Edge Computing системах - Єременко, О. С.; Круглова, А. О.; Журавльова, А. С.; Персіков, М. А. (ХНУРЕ, 2020)
An analysis of modern architectural approaches to complex resilience of distributed systems built using so called integrated cloud computing technologies, including Cloud, Fog, and Edge Computing, was conducted. Classes of solutions on resilience improvement, as well as threats to the resilience of infocommunication networks and means of its provision are covered. The task of developing a universal flexible system of control, monitoring, and response is formulated in order to identify possible degradation of the Quality of Service, resilience, and security in the network and take corrective action according to its architecture and types of services provided.
Keywords: якість обслуговування; Quality of Service; відмовостійкість; resilience; мережна безпека; cloud computing; Fog; network security